Direct and indirect effects of dominant plants on ecosystem multifunctionality - Chen, Jingwei; Liu, Ziyang; Cui, Hanwen; Song, Hongxian; Wang, Jiajia; Gao, Haining; Chen, Shuyan; Liu, Kun; Yang, Zi; Wang, Yajun; Wang, Xiangtai; Yang, Xiaoli; et al. (Frontiers in Plant Science, 2023)
Biodiversity is essential for the provision of multiple ecosystem functions simultaneously (EMF). Yet, it remains unclear whether and how dominant plant species impact ecosystem multifunctionality (EMF). Here, we aimed at disentangling the direct from indirect above- and belowground pathways by which dominant plant species influence EMF. We evaluated the effects of two dominant plant species (Dasiphora fruticosa, and the toxic perennial plant Ligularia virgaurea) with expected positive and negative impacts on the abiotic environment (soil water content and pH), surrounding biological communities (plant and nematode richness, biomass, and abundance in the vicinity), and on the EMF of alpine meadows, respectively. We found that the two dominant plants enhanced EMF, with a positive effect of L. virgaurea on EMF greater than that of D. fruticosa. We also observed that dominant plants impacted on EMF through changes in soil water content and pH (indirect abiotic effects), but not through changes in biodiversity of surrounding plants and nematodes (indirect biotic pathway). Our study suggests that dominant plants may play an important role in promoting EMF, thus expanding the pervasive mass-ratio hypothesis originally framed for individual functions, and could mitigate the negative impacts of vegetation changes on EMF in the alpine meadows.